Minimally invasive surgery in Crohn’s disease: state-of-the-art review - Liu, Wei; Zhou, Wei (Frontiers in Surgery, 2023)
Surgery for Crohn’s disease (CD) has undergone significant advancements over the last two decades, especially minimally invasive surgery. In addition to its feasibility and safety, minimally invasive surgery provides manifold advantages, including a decreased hospitalization duration, improved aesthetic results, and fewer occurrences of intra-abdominal adhesions. Due to the special intraoperative characteristics of CD, such as chronic inflammation, a thickened mesentery, ﬁstulas, abscesses and large masses, a minimally invasive approach seems to be challenging. Complete implementation of this technique for complex disease has yet to be studied. In this review, we provide a review on the applicability of minimally invasive surgery in CD and future perspectives for the technical advances in the field.